Synthesis of the historiography on philosophical Modernity in 18th-Century New Spain (Devenires, 2021)
Eigteenth-century philosophy in New Spain has been the object of a number of studies in which the main concern is the theme of Novohispanic philosophical modernity. A historiography of philosophy in colonial Mexico in the 1700s has consolidated, and it is possible to realize a synthesis about its exegetical results. The synthesis points to modernity as “eclecticism”: the reception of modern ideas in the context of a predominantly scholastic philosophy.
Keywords: scholasticism; renovation; eclecticism; Jesuits; Gamarra